La inclusión económica de los jóvenes al mercado laboral del ecuador, periodo 2009 - 2019. - Veliz Andrade, Melina Margarita (Machala : Universidad Técnica de Machala, 2021)
This article aims to analyze youth economic inclusion in the Ecuadorian labor market in the period 2009 to 2019, taking as reference information from secondary sources, corresponding to the compilation of investigative evidence such as the International Labor Organization (ILO), the Economic Commission for Latin America and the Caribbean (ECLAC), the Ministry of Labor, the National Institute of Statistics and Censuses (INEC), among other bibliographic reviews focused on the real situation that the majority of young people in the country go through, based on the results obtained establish the most relevant factors that determine employability, such as education, labor supply and demand, socio-economic conditions, labor institutions, among others, which as a consequence, has decreased full employment, underemployment and on the contrary, unemployment has increased.
El presente artículo tiene como objetivo analizar la inclusión económica juvenil en el mercado laboral del Ecuador en el periodo 2009 al 2019, tomando como referencia información de fuentes secundarias, correspondientes a la recopilación de evidencias investigativas como la Organización Internacional del Trabajo (OIT), la Comisión Económica para América Latina y el Caribe (CEPAL), el Ministerio de Trabajo, el Instituto Nacional de Estadística y Censos (INEC), entre otras revisiones bibliográficas enfocadas en la situación real que atraviesan la mayoría de los jóvenes en el país, en base a los resultados obtenidos se establecen los factores más relevantes que determinan la empleabilidad, como son la educación, la oferta y demanda laboral, las condiciones socio-económicas, instituciones labores, entre otros que como consecuencia, ha disminuido el pleno empleo, el subempleo y por lo contrario el desempleo ha aumentado.
Keywords: INCLUSIÓN; ECONÓMICA; MERCADO; LABORAL